Estilos educativos parentales y convivencia escolar en los niños de la Institución Educativa N° 454 Mi Casita del Saber, Nauta 2023 - Vasquez Upiachihua, Sidlia Maria (2023)
The purpose of this examination was to establish the relationship between parental educational styles and school life in children of the Initial Educational Institution No. 454 "Mi Casita del Saber" Nauta - 2022 This research is of a relational quantitative type. It has the non-experimental design. The population constituted by the 78 children and 78 parents of the Institution. Tools used to obtain data that have been previously validated through peer review. Conclusions: using the Spearman's rho rank correlation coefficient for ordinal samples, the result = 0.88, this value indicates a high positive relationship between both variables. Parental educational styles are significantly related to school life in children of the Initial Educational Institution No. 454 "Mi Casita del Saber" Nauta - 2022.